Gastric metastasis by primary lung adenocarcinoma - Okazaki, Ryota (Baishideng Publishing Group Co., Limited, 2010)
The diagnosis of gastric metastasis from lung cancer is relatively rare in living patients. We describe a case of Type 4 tumor-like metastasis due to primary lung cancer diagnosed with immunohistochemical staining while the patient was alive. A 68-year-old man was admitted to our hospital because of epigastric pain. Gastrointestinal endoscopy revealed a Type 4 tumor and the histological examination showed poorly differentiated adenocarcinoma. His chest X-ray showed mass shadow in the right upper lung field. The resected specimens showed moderately differentiated adenocarcinoma., The diagnosis of gastric metastasis from lung cancer was made by immunohistochemical staining of the lung and gastric tumors which showed positive staining for Thyroid transcriptional factor-1. Diagnosis of gastric metastasis, especially Type 4 metastasis by lung cancer is difficult. However, immunohistochemical staining is very helpful for diagnosis of primary lung cancer metastasis at sites such as the gastrointestinal tract which are not normally prone to metastatis.